HUBUNGAN DIABETES MELITUS (DM) TIPE 2 DENGAN KEJADIAN DEPRESI PADA PASIEN DM TIPE 2 OBESE DAN NON OBESE DI RSUP DR. SARDJITO YOGYAKARTA TAHUN 2013 - , RONNY RICHARDO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The purpose of this study is to find the correlation between type 2 diabetes mellitus and depression among obese and non-obese patients with type 2 diabetes mellitus in Sardjito Hospital Yogyakarta in 2013. 64 patients with type 2 diabetes mellitus in endocrinology clinic of Sardjito Hospital participated in this study (32 obese patients and 32 non-obese patients). The questionnaire of Beck Depression Inventory (BDI) in Bahasa Indonesia was used for depression evaluation. 22 (68,75%) obese patients with type 2 diabetes mellitus (n=32) and 13 (40,62%) nonobese patients with type 2 diabetes mellitus (n=32) were found to be depressed. The result of statistical analysis using chi-square (X2) method on SPSS system was p=0,024 (p<0,05), with contigency coefficient 0,272. Prevalence ratio of this research is 1,69 (95% CI 1,048 â 2,734). This result shows that there is a relation between type 2 diabetes mellitus and depression among obese and non-obese patients with type 2 diabetes mellitus in Sardjito Hospital Yogyakarta in 2013.